Effect of magnesium and calcium as spheroidizer on the graphite morphology in ductile cast iron (2007)
This study investigated the effect of magnesium and calcium as spheroidizers on the graphite microstructure in cast iron. The cast iron samples were melted in an induction furnace with charge of known composition and, magnesium and calcium of known percentages were added as spheriodizers to the molten metal in the mould during the casting process. From the microstructure of the as- cast specimens it was observed that the use of 100% Mg and a combined addition of 60% and 40%Ca as spheriodizers produced graphite spheroids instead of graphite flakes in the cast iron microstructure. The use of 100% Ca addition resulted in the production of graphite flakes in the specimen microstructure. The use of 80% Mg and 20% Ca resulted in the production of a chunky, stubby graphite microstructure, while the additions of 50% Mg and 50% Ca, 40%Mg and 60% Ca, and 20% Mg and 80% Ca resulted in the microstructure having a flaky graphite microstructure.